Andropogon gayanus var. bisquamulatus cv. Planaltina: principal forage characteristics - Thomas, Derrick; Andrade, Ronaldo P. de; Couto, Walter; Rocha, Carlos Magno Campos da; Moore, Patrick (Pesquisa Agropecuaria Brasileira, 2014)
Andropogon gayanus var. bisquamulatus (Hochst.) Hack. cv. Planaltina was released in Brazil in 1980 as an alternative species to signal grass (Brachiaria decumbens) for the acid, infertile soils of the Cerrados region. The cultivar originated in Nigeria and previously performed well in the Llanos of Colombia. The attributes of the cultivar are described, namely, its good adaptation to the climate and soils of the region, tolerance of fire, compatibility with legumes, good seed production potential, freedom from serious pests or diseases, good animal acceptability and live weight gains.